NRF2 Protection against Liver Injury Produced by Various Hepatotoxicants. (23rd May 2013) - Liu, Jie; Wu, Kai Connie; Lu, Yuan-Fu; Ekuase, Edugie; Klaassen, Curtis D.
Abstract : To investigate the role of Nrf2 as a master defense against the hepatotoxicity produced by various chemicals, Nrf2-null, wild-type, Keap1-knock down (Keap1-Kd) and Keap1-hepatocyte knockout (Keap1-HKO) mice were used as a "graded Nrf2 activation" model. Mice were treated with 14 hepatotoxicants at appropriate doses, and blood and liver samples were collected thereafter (6 h to 7 days depending on the hepatotoxicant). Graded activation of Nrf2 offered a Nrf2-dependent protection against the hepatotoxicity produced by carbon tetrachloride, acetaminophen, microcystin, phalloidin, furosemide, cadmium, and lithocholic acid, as evidenced by serum alanine aminotransferase (ALT) activities and by histopathology. Nrf2 activation also offered moderate protection against liver injury produced by ethanol, arsenic, bromobenzene, and allyl alcohol but had no effects on the hepatotoxicity produced by D-galactosamine/endotoxin and the Fas ligand antibody Jo-2. Graded Nrf2 activation reduced the expression of inflammatory genes (MIP-2, mKC, IL-1 β, IL-6, and TNF α ), oxidative stress genes (Ho-1, Egr1), ER stress genes (Gadd45 and Gadd153), and genes encoding cell death (Noxa, Bax, Bad, and caspase3). Thus, this study demonstrates that Nrf2 prevents the liver from many, but not all, hepatotoxicants. The Nrf2-mediated protection is accompanied by induction of antioxidant genes, suppression of inflammatory responses, and attenuation of oxidative stress.